Characterization of structure and Li-ionic conductivity of La\(_(2/3)−x\)Li\(_3x\)TiO\(_3\) ceramics prepared by spark plasma sintering - Le Dinh, Trong; Nguyen Huu, Tinh; Pham Van, Hao (Communications in Physics, 2023)
In this work, La(2/3)-xLi3xTiO3 (LLTO) dense ceramic samples have been prepared by high-energy ball milling and spark plasma sintering (SPS) route. The crystal structures and microstructures of the samples were characterized by X-ray powder diffraction and FE-SEM, whereas their Li-ionic conductivity properties investigated by AC impedance spectroscopy. At 21 oC, the LLTO ceramic samples possessed the grain conductivity and grain boundary/total conductivity of σg = 8.3×10-4 S cm-1 and σgb = 2.3×10-5 S cm-1, respectively. In the investigated temperature range from 21 oC to 120 oC, the ion conduction is governed by thermally activated mechanism. The activation energies for grain and grain boundary conductivities are Eag = 0.26 eV and Eagb = 0.43 eV, respectively.